Advances in controlled release of microcapsules and promising applications in self-healing of asphalt materials. (20th April 2021) - Lu, Tong; Li, Bin; Sun, Daquan; Hu, Mingjun; Ma, Jianmin; Sun, Guoqiang
Abstract: Asphalt aging and fatigue cracking are common forms of distresses in flexible pavements. Microencapsulated rejuvenator has been generating significant interest in the feasibility and potentiality applications of asphalt materials self-healing over the past decade and is likely to remain so for the foreseeable future. Despite multiple attempts, the prerequisite is crack propagation through the microcapsules and resulting in the broken shell, which is a passive release. Strategies toward self-healing of uncracked aged asphalt by microcapsules remain a significant challenge. Herein, numerous successful applications of controlled release microcapsules in other fields, including biomedical engineering, food industry, agriculture, smart coating, textile industry, and cosmetics, are classified and referenced. Special attention is given to the mechanisms of release and their triggers, followed by recent advances of microencapsulation technologies with detailed experimental demonstrations. In particular, the challenges and promising solutions of novel controlled release systems for asphalt materials are proposed in detail for the first time. This review aims to present future directions for research in this field, which provides new ideas for the smart maintenance of asphalt pavements.